Effects of Si/SiO2 interface stress on the performance of ultra-thin-body field effect transistors: a first-principles study. (6th December 2017) - Jung, Hyo-Eun; Shin, Mincheol
Abstract: First-principles density functional theory (DFT) based device simulations are performed for Si ultra-thin-body (UTB) field effect transistors with the explicit SiO2 atoms in the gate dielectric. In order to evaluate the Si/SiO2 interface stress effects on the UTB device performance, the interface stress tensor is extracted from the Si/SiO2 atomic structure by DFT calculations. The influence of the interface stress on the transport properties is examined through full quantum mechanical non-equilibrium Green's function calculations. Based on the analysis of the band structure and transfer characteristics, we demonstrate that the interface stress can characterize the overall effects of the SiO2 gate dielectric on the device performance in the nanoscale regime.